Phylogenomics using Target-Restricted Assembly Resolves Intrageneric Relationships of Parasitic Lice (Phthiraptera: Columbicola). (6th March 2017) - Boyd, Bret M.; Allen, Julie M.; Nguyen, Nam-Phuong; Sweet, Andrew D.; Warnow, Tandy; Shapiro, Michael D.; Villa, Scott M.; Bush, Sarah E.; Clayton, Dale H.; Johnson, Kevin P.
Abstract : Parasitic "wing lice" (Phthiraptera: Columbicola ) and their dove and pigeon hosts are a well-recognized model system for coevolutionary studies at the intersection of micro- and macroevolution. Selection on lice in microevolutionary time occurs as pigeons and doves defend themselves against lice by preening. In turn, behavioral and morphological adaptations of the lice improve their ability to evade host defense. Over macroevolutionary time wing lice tend to cospeciate with their hosts; yet, some species of Columbicola have switched to new host species. Understanding the ecological and evolutionary factors that influence coadaptation and codiversification in this system will substantially improve our understanding of coevolution in general. However, further work is hampered by the lack of a robust phylogenetic framework for Columbicola spp. and their hosts. Previous attempts to resolve the phylogeny of Columbicola based on sequences from a few genes provided limited support. Here, we apply a new approach, target restricted assembly, to assemble 977 orthologous gene sequences from whole-genome sequence data generated from very small, ethanol-preserved specimens, representing up to 61 species of wing lice. Both concatenation and coalescent methods were used to estimate the species tree. These two approaches yielded consistent and well-supported trees with 90% of all relationships receiving 100% support, which is a substantial improvement over previous studies. We used this new phylogeny to show that biogeographic ranges are generally conserved within clades of Columbicola wing lice. Limited inconsistencies are probably attributable to intercontinental dispersal of hosts, and host switching by some of the lice. [aTRAM; coalescent; coevolution; concatenation; species tree.]